A Model of Academic Services Quality at Advent Schools in North Sulawesi Province - Freida Ferra Masoko; Henny Tambingon; Harold Lumapow; Jeffry S. J. Lengkong (International Journal of Social Service and Research (IJSSR), 2023)
The quality of academic services is one of the determining factors for improving student learning outcomes in schools. This study aims to explain and predict the model of academic service quality in Adventist Schools in North Sulawesi Province. This study uses a quantitative approach and survey methods. The sampling technique for this research was randomly selected and totaled 172 teachers spread over eight Adventist schools in North Sulawesi Province. The research data were collected using a questionnaire technique and analyzed using the Structural Equation Modeling technique based on Partial Least Square (SEM-PLS) with smartPLS 3.0 software. The results showed that the principal's managerial competence, compensation, and teacher performance had a direct and significant positive effect on the quality of academic services. While the role of the school committee has a direct negative and insignificant effect. In addition, teacher performance mediates the effect of principal's managerial competence on the quality of academic services. Meanwhile, the influence of the role of the school committee and the provision of compensation on the quality of academic services is not mediated by teacher performance. The results of the research that describe the academic service quality model in this study are discussed and conclusions are drawn. After that, suggestions were made for programs to improve the quality of academic services and future research efforts.